Integration of VSD-Based Spinner Machines to Increase Efficiency and Product Quality at Alfin Kripik Seboro UMKM - Caesar Adlu Hakim; Moh. Zainul Falah; Wahyu Tri Handoko; Ghasa Faraasyatul ‘Alam; Raffi Taufik Gushardana; Sucipto (CV. Creative Tugu Pena, 2024)
Alfin Seboro Kripik is a Micro, Small, and Medium Enterprise (UMKM) that is engaged in the production of Seboro chips, a traditional Indonesian snack made from cassava. Alfin Seboro Kripik strives to uphold its heritage while adapting to modern market demands. This UMKM uses manual and traditional methods to make its chips, relying on a manual process involving frying and seasoning. Despite its commitment to tradition, Alfin Seboro Kripik faces challenges related to product quality and efficiency in its production line. One important issue is the adhesion of oil to the chips after frying, which affects the taste and texture of the final product. Additionally, the lack of advanced machinery limits the company's ability to meet rising consumer expectations and compete effectively in the marketplace. Realizing the need for innovation and improvement, Alfin Seboro Keripik hopes that there will be efforts to integrate modern technology such as the Variable Speed Drive (VSD) Based Spinner Machine system into its production process. The introduction of VSD-driven spinning machines aims to improve oil removal efficiency, improve product consistency, and optimize production workflows. By embracing innovation, Alfin Seboro Kripik aims to improve quality standards, expand market reach, and contribute to the economic development of local communities.